2020
DOI: 10.3390/ijerph17072302
|View full text |Cite
|
Sign up to set email alerts
|

Experience and Awareness of Health Managers, Administrators, and Workers on a Hearing Conservation Program in Korea: A Qualitative Study

Abstract: This study aims to evaluate the experience and awareness of a hearing conservation program to explore its activation plan. Three focus group discussions were conducted with five health managers, five labor supervisors, and five workers. A single in-depth interview was conducted with a health manager. Since hearing loss has a significant influence on the quality of life of workers, all participants recognized the importance of management. Although the need for hearing conservation programs was acknowledged, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Quantitative research, which focuses on hypothesis validation, such as the superiority of specific treatments or the effectiveness of specific policies, and the generalization of findings, has been the primary research methodology in the field of healthcare. Qualitative research has been mostly applied for studies such as subjective disease experiences and attitudes with respect to health-related patient quality of life [10][11][12], experiences and perceptions regarding the use of healthcare services [13][14][15], and assessments of the quality of care [16,17]. Moreover, qualitative research has focused on vulnerable populations, such as the elderly, children, disabled [18][19][20], minorities, and socially underprivileged with specific experiences [21,22].…”
Section: Applications Of Qualitative Research and Its Usefulness In T...mentioning
confidence: 99%
“…Quantitative research, which focuses on hypothesis validation, such as the superiority of specific treatments or the effectiveness of specific policies, and the generalization of findings, has been the primary research methodology in the field of healthcare. Qualitative research has been mostly applied for studies such as subjective disease experiences and attitudes with respect to health-related patient quality of life [10][11][12], experiences and perceptions regarding the use of healthcare services [13][14][15], and assessments of the quality of care [16,17]. Moreover, qualitative research has focused on vulnerable populations, such as the elderly, children, disabled [18][19][20], minorities, and socially underprivileged with specific experiences [21,22].…”
Section: Applications Of Qualitative Research and Its Usefulness In T...mentioning
confidence: 99%
“…A discussion with the top management on the outcome of pre-HCP revealed that the management was not aware of the obligation to conduct HCP in the institution. Little to no awareness and knowledge on noise regulation and HCP among the management and educators in the institution significantly affects the HCP compliance [34,63]. The management admitted that some of the preventive measures were implemented to comply with general safety regulations and not noise regulation specifically.…”
Section: Hcp Components Conformity Assessment and Ohci Systemmentioning
confidence: 99%
“…Small and medium industries (SMI) employers dutifully provide HPDs, but neglect other components of HCP, especially noise control measures [32][33][34]. The employers are unaware that the effectiveness of one size to fit everyone HPD in protecting users against harmful noise remains questionable.…”
Section: Introductionmentioning
confidence: 99%